Translation of Wages and the Exchange Rate - a Pragmatic Study - Jędrzejczyk, Marcin; Jędrzejczyk, Anna (Translacja wynagrodzeń a kurs walutowy - studium przypadku, 2011)
As recent studies show the direct implication of the exchange rate to conversion of goods' prices, assets, GNP, GNP per capita or wages is inappropriate. The paper presents two different studies in case of Poland and the US and between Poland and the UK. The first study compares salaries of scientists in Polish and American universities, the second wages of doctors in different stages of education in Poland and the UK. This has been compared to average prices of chosen goods' basket to study purchasing power of remuneration in healthcare sector in Poland and the UK. The aim of the study is to show that direct implementation of the exchange rate category in translation process is in most cases inappropriate. Instead exchange rate multiplied by the relation between GNP per employee expressed in US dollars can be used.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 19-28
Keywords: exchange rate; translation; conversion; international comparisons